Speed Sensorless Control Method Using Improving MRAS Technique for Three-phase Induction Motor Drive - Trần Trọng Đạo; Đinh Hoàng Bách; Trần Đình Cương (Journal of Technical Education Science, 2024)
In this paper, a Speed Sensorless control method based on an improved reference model response system (RF_MRAS) is applied to estimate the rotor speed and parameters. control in the flux-oriented control (FOC) technique of three-phase induction motors (IM). This estimation speed is improved by enhancing the stator resistance (Rs) estimation step in the RF_MRAS model to improve the performance of the control method when Rs changes during operation. The proposed control method helps the system operate at precise speed, low overshoot, can quickly switch speed status at will, low starting current and relatively small starting torque. Together with the combination of estimating the stator resistance, the system can operate stably even when the parameters in the motor change. Experimental results on the operating model in MATLAB/SIMULINK environment have demonstrated the effectiveness of the proposed method in different operating conditions of three-phase induction motors with very good estimated speed tracking. relative to the applied speed, even when the applied speed changes rapidly.